Perianal Care Proven to Reduce the Incidence of Diaper Dermatitis - Lina Mahayaty1, Nani Nurhaeni2 , Dessie Wanda2 , Fitriah3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Maintaining a clean perianal area is an attempt to prevent and treat diaper dermatitis. The purpose of cleaningthe perianal area is to prevent irritation. The practice of cleaning the perianal area is done by consideringthe physiology of the skin such as, normal flora, bacteria, and skin pH. Cleaning the perianal area can usewater and a soft cloth without rubbing the skin hard. The purpose of applying evidence based in nursingpractice is to identify the effect of perianal care by using water against diaper dermatitis with skin integrityissues. Search evidence of nursing practice used the PICO analysis. Thirty-four toddlers were divided intotwo groups: the intervention group (n = 17) and the control group (n = 17). The analysis used was Wilcoxon,and Mann-Whitney test. There was no significant difference in diaper dermatitis score in the interventiongroup and control group (?> 0.05). Cleaning the perianal area using water and tissues can be used to preventand treat diaper dermatitis.